APPLICATION OF PROTOTYPE METHOD IN PERIODIC SERVICE INFORMATION SYSTEM APPLICATION (Case Study: MELET TUNING WORKSHOP MEDAN) - Ramadini, Dwi Wulan Indah; Zakir, Ahmad; Sembiring, Boni Oktaviana (Bahasa Indonesia, 2025)
This study aims to build a website-based periodic service information system application, By applying the prototype method application development method through concepts, design, and evaluation provides solutions to problems. It was found that the use of periodic service applications in the Melet Tuning Medan workshop, which has been built is very useful because of the results of the application of methods and system design. can create satisfaction with the workshop's services to customers. get service and the workshop can manage service data well and efficiently. This study produces a prototype design and applies methods in building periodic service applications on the website system.